PENGEMBANGAN METODE ALTERNATIF UNTUK PENGOLAHAN DATA KERANGKA HORIZONTAL TELITI - Dzun Nurwinas S, Muhammad
Terrestrial measurement methods are still often used in large-scale mapping. For example in the construction of bridges that are far away. Of course, it requires a precise horizontal traverse for mapping. Therefore, the implementation of the procurement of the horizontal traverse must be in accordance with the rules. Including the process of reducing the measurement of the terrestrial in data processing. But in reality the reduction process cannot be carried out because in its formulation the reduction process requires coordinates and elevations at the points being measured for distances and angles, which is the purpose of the terrestrial survey itself. Therefore, it is necessary to use another method so that the terrestrial data processing process can obtain more accurate results without carrying out a reduction process. In this study, an alternative method was formulated in which the big idea was how to define an ellipsoid that coincided with the measurement area. Thus, the terrestrial measurement can be considered as the measurement on the surface of the ellipsoid. The working steps of this alternative method are explained in depth in this final project. The outputs of this alternative method are local datum parameters, temporary projection system parameters, and horizontal baseline control point coordinates defined in a temporary projection system with local datums. The use of this alternative method shows better results, as seen from the resulting distance and angle closure errors, than without using this alternative method.